2003
DOI: 10.2109/jcersj.111.433
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Surface Reaction of Highly Oriented Anatase Polycrystalline Films Synthesized Using a CVD Apparatus Operated in Atmospheric Regime

Abstract: åCJú^»wCÍoujì»T^züAE»ô¸½»mõUN\ʽ cCñÞ Þ Ec³YÞ EåÎvÞ Þ EÖ¡GrÞ ÞHighrate growth of polycrystalline anatase lms was achieved on nonepitaxial substrates using a chemical vapordeposition technique operated under air atmosphere. As the growth rate of each crystalline face was strongly dependent on the deposition conditions, four types of anatase polycrystalline lms were fabricated with several oriented directions such asq112r , q110r , q100randq001r . The photoinduced surface reaction of the anatase lms was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It thus appears that the photo-oxidation rate of carboxylates is highest on anatase particles in the size range 25-50 nm and is due to the smaller concentration of m-formate and bicarbonate species formed on these particles. The fundamental reason for their high activity is not known, but the discussion here and in the previous section strongly suggests that structure sensitive bonding and reactivity play important roles, qualitatively similar to what has been inferred for preferentially oriented TiO 2 thin films and facetted macrocrystals [142][143][144][145][146][147].…”
Section: Photoreactions With Tiosupporting
confidence: 75%
See 1 more Smart Citation
“…It thus appears that the photo-oxidation rate of carboxylates is highest on anatase particles in the size range 25-50 nm and is due to the smaller concentration of m-formate and bicarbonate species formed on these particles. The fundamental reason for their high activity is not known, but the discussion here and in the previous section strongly suggests that structure sensitive bonding and reactivity play important roles, qualitatively similar to what has been inferred for preferentially oriented TiO 2 thin films and facetted macrocrystals [142][143][144][145][146][147].…”
Section: Photoreactions With Tiosupporting
confidence: 75%
“…On anatase TiO 2 nanoparticles, there appears to be a correlation between the reactivity and the detailed morphology and surface structure [142][143][144][145][146]. T. Taguchi et al [147] recently reported that photocatalytic reduction of PtCl 6 2À in 2-propanol resulted in Pt deposition on (101) facets, while PbO 2 deposited on (112) facets upon photocatalytic reduction of Pb 2 þ in 2-propanol, suggesting that (101) facets provide reductive sites and (112) oxidative sites.…”
Section: Photoreactions Of Hcooh On Tiomentioning
confidence: 99%
“…For instance, the crystal morphology destabilizes; that is, continuous film surfaces roughen with increasing supersaturation (Tokita, Tanaka, & Ohshio, 2003;Tokita, Tanaka, & Saitoh, 2000). The surface and cross-sectional SEM images of the deposited films are shown in Figures 2 and 3.…”
Section: Morphological Studymentioning
confidence: 99%
“…Atmospheric-pressure chemical vapor deposition (CVD) is a method of depositing high-quality metal oxide films onto various substrates at atmospheric pressure and without requiring a vacuum system (Saitoh, Okada, & Ohshio, 2002;Saitoh, Takano, Kawaguchi, Washio, Ohshio, & Akasaka, 2009;Akasaka et al, 2013;Sugata et al, 2003;Satoh et al, 2002;Satou et al, 1999;Saitoh, Fukada, & Ohshio, 2003;Tokita, Tanaka, & Ohshio, 2003;Tokita, Tanaka, & Saitoh, 2000). Further, the atmospheric-pressure CVD apparatus is inexpensive and can be used to deposit uniform, homogeneous, dense films showing high coverage, tunable chemical compositions and morphologies, and no uncoated "hidden areas."…”
Section: Introductionmentioning
confidence: 99%
“…In atmospheric CVD, metal-containing organic complexes are used as metal sources for oxide films. For examples, bis-magnesium acetylacetonate can be used as the Mg source for MgO films (Saitoh, Okada, & Ohshio, 2002) and titanium tetraisopropoxide (TTIP) can provide Ti for TiO 2 films (Tokita et al, 2003), using atmospheric CVD techniques. The atmospheric CVD setup is, fundamentally, a thermal CVD type.…”
Section: Introductionmentioning
confidence: 99%